Correction to: Antimalarial combination therapies increase gastric ulcers through an imbalance of basic antioxidative-oxidative enzymes in male Wistar rats - Muhamudu Kalange; Miriam Nansunga; Keneth Iceland Kasozi; Josephine Kasolo; Jackline Namulema; Jovial Kasande Atusiimirwe; Emmanuel Tiyo Ayikobua; Fred Ssempijja; Edson Ireeta Munanura; Kevin Matama; Ibrahim Semuyaba; Gerald Zirintunda; et al. (BMC Research Notes, 2020)
An amendment to this paper has been published and can be accessed via the original article.